Attractiveness of Pitfall Traps with Baits for Harvestmen in a Sugarcane Agroecosystem - Peixoto, Pedro Gomes [UNESP]; Nascimento, Vinícius Ferraz [UNESP]; de Lacerda, Letícia Barbosa [UNESP]; Siansi, Frederico Luiz; de Matos, Gilson Fabiano; de Souza, Joice Mendonça [UNESP]; Ramalho, Dagmara Gomes [UNESP]; De Bortoli, Sergio Antonio [UNESP] (Springer Nature, 2024)
Harvestman belong to a diverse order of arachnids associated with soil fauna, containing various invertebrate organisms that have a relationship with the soil, directly influencing its physical and chemical characteristics, and providing important ecosystem services. This study investigates the presence of harvestman in sugarcane crop fields, using two types of traps with different attractants. The research was conducted in Jaboticabal, São Paulo, Brazil, a region known for its agricultural landscapes, primarily characterized by sugarcane crops. The results obtained show that the species Liogonyleptoides inermis dominates the study area, and pitfall traps proved to be highly effective in capturing these arachnids, especially those associated with couples of Sphenophorus levis, a pest of great economic importance for the region. This research highlights the presence and distribution of these arachnids in agricultural landscapes, emphasizing the potential relationship between them and the sugarcane environment, as well as their role as a primary as predators of insect pest. It underscores the need for further in-depth studies involving these animals and their relationships within the sugarcane agroecosystem.
Keywords: attractiveness; bicudo da cana-de-açucar; edaphic fauna; Liogonyleptoides inermis; Sphenophorus levis; traps